The Influence of Political Party Funds on the Acquisition of seats in the DPR RI in the legislative elections - Andi Faisal; Siswadi Sululing; Asrini; Arif Masruhi (Jurnal Economic Resource, 2021)
This article provides evidence of the relationship between the expenditure of campaign funds for political parties participating in the 2019 legislative general election and the acquisition of the number of seats in the Indonesian People's Representative Council (DPR RI). Theoretically, campaign funds affect the number of votes. This is supported by several previous studies both domestically and abroad. Data on the use of campaign funds for all political parties participating in the 2019 legislative elections were obtained from the Central General Elections Commission (KPU) website page. The data were obtained using SPSS version 20 statistical data processing program with simple regression analysis. The results showed that the R Square value was 0.685. This value implies that the effect of political party campaign funds on the acquisition of seats in the DPR RI for political parties is 68.5%. In comparison, 31.5% of the seats in the DPR RI for political parties are influenced by other variables not examined. This article can be considered for policymakers regarding political party campaign funds in the upcoming general election.